Trust violations in buyer–supplier relationships: Spillovers and the contingent role of governance structures. Issue 3 (11th July 2021) - Eckerd, Stephanie; Handley, Sean; Lumineau, Fabrice
Abstract: Buyer–supplier relationships provide ample opportunities for trust violations to occur. Yet the literature on the impact and outcomes of violations of trust in buyer–supplier relationships is underdeveloped. In this study, we report the results from three complementary scenario‐based experiments that evaluate the impact of a supplier‐induced violation on a buyer's trust in that supplier. We establish a spillover effect of supplier integrity violations onto the buyer's competence dimension of trust, and of supplier competence violations onto the buyer's integrity dimension of trust. We also examine the role of inter‐organizational governance, finding that contractual and relational governance are differentially effective at mitigating trust damages experienced by a buyer after a supplier violation. Specifically, we observe that relational governance helps mitigate damages to buyer's trust following a supplier competence violation, whereas some evidence suggests that contractual governance serves to preserve buyer's trust following a supplier integrity violation. These findings have important theoretical and managerial implications for the management of buyer–supplier relationships. We discuss why the governance structures adopted by firms involved in a buyer–supplier relationship have distinct impacts on trust assessments following a violation.